Implementation and Evaluation of Safe Handling Precautions Training for Oncology Nurses: An Experimental Design - Sevcan Topçu; Ayşe Beşer; Osman Alparslan Ergör; Sibel Konyalıoğlu (KHD-Production, 2022)
Antineoplastic drugs are a hazard for both patients and healthcare workers. Health workers may be exposed to antineoplastic drugs by inhalation, ingestion or direct skin contact during the preparation, transport, administration, storage and disposal of antineoplastic drugs. The study aims to evaluate the impacts of the training on the safe handling precautions and oxidative stress parameters for oncology nurses. The study was an experimental study without a control group. This study included 23 oncology nurses who were involved in the preparation and administration of antineoplastic drugs. Training effectiveness was evaluated with the safe handling precautions questionnaire and blood samples of oncology nurses. After the training, the frequency of using the closed system transfer devices and changing the chemotherapy glove every 30 min in preparation of antineoplastic drugs significantly increased in the post-test. The post-test 8-hydroxy-2′-deoxyguanosine mean of the nurses was found to be significantly lower than pre-test and follow-up. The training program provided a positive contribution to increasing the use of safe handling precautions and reducing oxidative damage. According to the results of this study, the training program can be used to develop protective health behaviors, and to reduce occupational exposure.